Macroeconomic Developments and the Influence of Inflation on the Performance of Small and Medium-Sizen Enteprises and Entrepreneurship in Serbia - Penezić, Nenad D; Jurakić, Marko (Poslovna ekonomija, 2024)
ABSTRACT: Today, entrepreneurs and small businesses (SMEEs) represent a driving force of the national economy, a key component of the innovation cycle and knowledge transformation into new products and processes. The importance of this sector is well recognized due to its significant contribution to gratifying various socio-economic objectives, such as job creation and employment possibilities, poverty reduction, inclusive growth of the economy, social cohesion and fostering entrepreneurship (innovations, ideas, skills). SMEEs also increase competition among themselves, heat up the market scenario and represent vital subcontractors to large enterprises (’the elephant and bee alliance’). At the same time, throughout recent history, this sector has shown exceptional toughness and resistance to crises, risks, uncertainty and insecurity. Today, the global economy faces an exceptional moment of uncertainty. Geopolitical risks will be the key threat to the economic outlook for 2024. Rising geopolitical tensions and global financial risks, high inflation, tightening monetary and fiscal policies, labour shortages, high trade barriers and slowing integration into global value chains all contribute to a more challenging business environment for SMEEs. High and persistent inflation has become a clear and present danger for many countries around the world. The aim of this paper is to analyse how recent changes in macroeconomic environment in Serbia, expecially inflation, affect the dynamics and challlenges of SMEE economic performance in the short and medium terms.
Keywords: SMEs, entrepreneurship, developing economies, macroeconomic development, inflation rate, economic growth.